1997
DOI: 10.1074/jbc.272.36.22966
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Cleavage of the mdm2 Oncoprotein during Apoptosis

Abstract: The mdm2 oncogene encodes a 90-kDa protein that can bind to the p53 tumor suppressor protein and negatively regulate its functions in transcription, cell cycle arrest, and apoptosis. The mdm2 gene is frequently amplified in human sarcomas, which may be responsible for the malignant transformations. We present evidence that the mdm2 oncoprotein is cleaved by an interleukin 1␤-converting enzyme-like protease (caspase) during p53-mediated apoptosis. The protease that cleaves mdm2 has a specificity similar to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
126
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(133 citation statements)
references
References 58 publications
5
126
0
2
Order By: Relevance
“…The evidence that eIF4G is degraded by a caspasemediated mechanism in response to a variety of apoptotic stimuli suggests that the initiation factor is a potential candidate to be added to the growing list of proteins that are cleaved by caspases (Martin and Green, 1995;Hale et al, 1996;Lavin et al, 1996;Chen et al, 1997;Widmann et al, 1998). However the e ects of the inhibitors Z-VAD.FMK and Z-DEVD.FMK are not su cient to indicate which caspase activity is responsible, or indeed to establish that these enzymes are the actual catalysts of eIF4G cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence that eIF4G is degraded by a caspasemediated mechanism in response to a variety of apoptotic stimuli suggests that the initiation factor is a potential candidate to be added to the growing list of proteins that are cleaved by caspases (Martin and Green, 1995;Hale et al, 1996;Lavin et al, 1996;Chen et al, 1997;Widmann et al, 1998). However the e ects of the inhibitors Z-VAD.FMK and Z-DEVD.FMK are not su cient to indicate which caspase activity is responsible, or indeed to establish that these enzymes are the actual catalysts of eIF4G cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified many substrates of caspases that play a role in cell cycle progression, such as cyclin E (43), Cdc2 (44), Cdc27, Wee1 (45), pRb (46), and MDM2 (47). Cleavage of these substrates invariably caused their inactivation and was associated with apoptotic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of formation of p60(MDM2) is still unclear. However, Chen et al 34) reported that MDM2 was cleaved by an caspase 3-like enzyme, leading to the accumulation of MDM2 with apparent molecular weight 60 kDa, with loss of 361 amino acids. This truncated form of MDM2 could bind to p53, but failed to promote p53 degradation due to the lack of the ring finger domain at the C-terminus, thereby apparently stabilizing p53 in a dominant-negative fashion.…”
Section: Discussionmentioning
confidence: 99%